2002
DOI: 10.1016/s0014-5793(02)03755-9
|View full text |Cite
|
Sign up to set email alerts
|

Loss‐of‐function and residual channel activity of connexin26 mutations associated with non‐syndromic deafness

Abstract: Connexins are the protein subunits of gap junction channels that allow a direct signaling pathway between networks of cells. The speci¢c role of connexin channels in the homeostasis of di¡erent organs has been validated by the association of mutations in several human connexins with a variety of genetic diseases. Several connexins are present in the mammalian cochlea and at least four of them have been proposed as genes causing sensorineural hearing loss. We have started our functional analysis by selecting ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
157
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(166 citation statements)
references
References 71 publications
8
157
1
Order By: Relevance
“…A series of in vitro studies, including protein expression study, cell-to-cell communication properties, or physiological conductance experiments, sometimes provided discrepant results when compared to the phenotypic results, and limitations have been suggested (see discussion in Cryns et al 2004). In the case of V37I, a complete loss of junctional properties has been reported (Bruzzone et al 2003) in spite of a rather mild phenotype shown in a series of studies. The protein expression experiments in the current study, however, were in line with the phenotype associated with this mutation.…”
Section: Discussionmentioning
confidence: 99%
“…A series of in vitro studies, including protein expression study, cell-to-cell communication properties, or physiological conductance experiments, sometimes provided discrepant results when compared to the phenotypic results, and limitations have been suggested (see discussion in Cryns et al 2004). In the case of V37I, a complete loss of junctional properties has been reported (Bruzzone et al 2003) in spite of a rather mild phenotype shown in a series of studies. The protein expression experiments in the current study, however, were in line with the phenotype associated with this mutation.…”
Section: Discussionmentioning
confidence: 99%
“…This polymorphism has been shown to confer loss of function on connexin 26 in vitro. 19 Phenotypic variation in expression of GJB2 mutations does suggest the possibility of modification of expression by other genes and environmental influences, 20 such as the digenic inheritance seen with GJB6 deletion. 11 However there are no reports of autosomal dominant effects from V37I, and the small sample size in our study makes it inappropriate to assume that V37I might contribute to recidivism.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations that result in no formation of GJs in the cell membrane include R143W, V153I and L214P, W77R (10,32). Many more Cx26 point mutants, e.g., V37I, L90P, S113R, delE120, M163V, R184P, 235delC, W44S, G59A, D66H, R75W, and R127H (8,9,33), are incorporated into GJs in the membrane. They interfere with either alignment of connexons or GJ permeability to abolish normal intercellular communications.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the K ϩ recycling theory, some Cx26 mutations are found to nullify the GJ conductance. However, some deafness-linked Cx mutants (T8M, V84L, V95M, and N206S) do not significantly affect GJ-mediated intercellular ionic coupling (8)(9)(10). A recent report further shows that the V84L mutant impairs GJ permeability to inositol 1,4,5-trisphosphate (IP 3 ) (11).…”
mentioning
confidence: 99%